Bridging the gap: Understanding Spanish society’s perception of purpose-driven companies and their role in sustainable development. - Ruiz-Mora, Isabel María; Guerrero-Navarro, Daniel; Lucía-Casademunt, Ana María (Universidade da Beira Interior, 2024)
This study explores Spanish society’s perspective on purpose-driven businesses as a sustainable model. Also, it assesses Spain’s commitment to sustainability and aligns corporate expectations with citizen respon-sibilities for societal and environmental betterment. A survey spanning 2021-2022 gauges citizen knowledge and attitude evolution towards these companies. Re-sults reveal 63% of the population is unaware of such businesses, but 74% deem them necessary upon unders-tanding. About 64.5% undertake small daily actions for planetary care, but only 12.8% cease purchasing from environmentally harmful companies. This paper provi-des empirical evidence of the link between corporate purpose and business sustainability in Spain, and ci-tizen perception of this business model’s impact and significance. It lays a theoretical and practical groun-dwork for future in-depth studies on purpose-driven companies
CC BY-NC-ND
Keywords: Desarrollo sostenible; Responsabilidad social de la empresa; Purpose-driven companies; Citizenship; Sustainable development; B corporations; Spain